Numerical two-dimensional flexible channel model fixed at both ends for flow-induced instability analysis - Lai, Lawrence; Elliott, Novak; Lucey, Anthony; Pitman, Mark (Engineers Australia, 2010)
The proposed study arises from a fluid-structure interaction (FSI) paradox of whether a fluid-conveying flexible channel fixed at both ends can experience flutter instability. Following the initial identification of this paradox in the 1970s, there have been findings that support the occurrence of flutter, both experimentally and analytically. Substantial evidence has also accumulated refuting the possibility of flutter occurring. Presently, this issue has yet to be satisfactorily resolved. In this paper a model of a two-dimensional channel with a flexible segment pinned at both ends is developed. The governing equations for the fluid, solid and their interaction are detailed as well as the specifics of their numerical solution. Preliminary results demonstrate the validity of the numerical model. This paper establishes the framework for a more detailed investigation of the FSI system.